EKSPERIMENTASI MODEL PEMBELAJARAN KOOPERATIF TIPE TWO STAY TWO STRAY DENGAN PENDEKATAN SAINTIFIK (TSTS-PS) DAN TIPE TEAMS ASSISTED INDIVIDULIZATION DENGAN PENDEKATAN SAINTIFIK (TAI-PS) PADA MATERI HIMPUNAN DITINJAU DARI KECEMASAN BELAJAR MATEMATIKA SISWA - Ratnasari Ratnasari; Mardiyana Mardiyana; Budi Usodo (Universitas Sebelas Maret, 2015)
Abstract: This research aimed to find out: (1) which one is better among cooperative learning models of TSTS with scientific approach (TSTS-PS), TAI with scientific approach (TAI-PS) or classical with scientific approach one in giving mathematics learning achievement, (2) which one is better among students’ anxiety categories, students having high, middle or low categories giving mathematics learning achievement. (3) in each learning model, which one is better among students’ anxiety categories in giving mathematics learning achievement and (4) in each anxiety categories, which one is better among TSTS with scientific approach (TSTS-PS), TAI with scientific approach (TAI-PS) or classical with scientific approach in giving mathematics learning achievement. This research was the quasi-experimental research with 3×3 factorial design. The population of research was all grade VII students of Junior High School (SMP) in Karanganyar Regency. The samples were chosen by using stratified cluster random sampling. The instruments that were used to collect the data were the test of mathematics achievement and questionnaire of students’ anxiety categories. Prior knowledge data are examined by using one-way ANOVA with unbalanced cells. It shows that three classes have balance prior knowledge. Meanwhile, the technique of analyzing the data was two-ways ANOVA with unbalanced cells. The result of research showed as follows. (1) The TSTS-PS had better learning achievement than the TAI-PS and classical with scientific approach. TAI-PS had learning achievement as good as the classical with scientific approach, (2) The students having low anxiety categories had better learning achievement than those having middle and high categories. The students having middle anxiety categories had learning achievement as good as those having high categories. (3) In each learning models, the students having low anxiety categories had better learning achievement than those having middle and high categories. The students having middle anxiety categories had learning achievement as good as those having high categories. (4) In each of students’ anxiety categories, the TSTS with scientific approach had better learning achievement than the TAI and classical with scientific approach. TAI with scientific approach had learning achievement as good as the classical with scientific approach.Keywords : Two Stay Two Stray (TSTS), Teams Assisted Individulization (TAI), Classical, Scientific Approach, Students’ Anxiety.